2021
DOI: 10.1080/07315724.2020.1856013
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency and Low Serum Calcium as Predictors of Poor Prognosis in Patients with Severe COVID-19

Abstract: Background: The severity of Coronavirus Disease 2019 (COVID-19) is a multifactorial condition. An increasing body of evidence argues for a direct implication of vitamin D deficiency, low serum calcium on poor outcomes in COVID-19 patients. This study was designed to investigate the relationship between these two factors and COVID-19 in-hospital mortality. Materials: This is a prospective study, including 120 severe cases of COVID-19, admitted at the department of Reanimation-Anesthesia. Vitamin D was assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 25 publications
1
70
0
5
Order By: Relevance
“…Established risk factors for severe COVID-19 include advanced age, obesity, chronic illness, non-Caucasian ethnicity, and work-related contact with COVID-19 patients (6). Furthermore, several studies suggest that genetic factors [5] and vitamin D deficiency [6,7] may also increase the risk for severe COVID-19-and SARS-CoV-2-related mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Established risk factors for severe COVID-19 include advanced age, obesity, chronic illness, non-Caucasian ethnicity, and work-related contact with COVID-19 patients (6). Furthermore, several studies suggest that genetic factors [5] and vitamin D deficiency [6,7] may also increase the risk for severe COVID-19-and SARS-CoV-2-related mortality.…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review and meta-analysis, hypocalcemia was related to poor prognosis, and the mean difference in serum calcium levels among patients with poor outcomes (26%) was 0.69 mg/dL [165]. Given the importance of calcium-phosphorus metabolism in this clinical scenario, Bennouar et al found that a cutoff value of 16 ng/mL for VD and 8.2 mg/dL for corrected calcium could predict poor prognosis (hazard ratios 6.9 and 6.2, respectively) in COVID-19 patients with a sensitivity of 76% and 84% and a specificity of 69% and 60%, respectively [166].…”
Section: Parathyroid Glands and Calcium-phosphorus Metabolismmentioning
confidence: 99%
“…Of these, 653 studies were duplicate articles or were excluded based on predetermined eligibility criteria during title/abstract review. According to the inclusion and exclusion criteria, we identified 11 studies [23,24,33,[25][26][27][28][29][30][31][32] that were eligible for this review and meta-analysis (Fig. 1), involving 1,347 participants.…”
Section: Characteristics Of the Selected Studiesmentioning
confidence: 99%
“…1), involving 1,347 participants. Ten were cohort [23,24,[26][27][28][30][31][32][33], and one case-control [25]. The characteristics of selected studies and participants are summarised in Table 1.…”
Section: Characteristics Of the Selected Studiesmentioning
confidence: 99%